Makna Hijrah Dalam Tafsir Fi Zhilal Al-Qur’an Karya Sayyid Quthb - M Maskun Hadi; Muhajirin Muhajirin; Kusnadi Kusnadi (Jurnal Semiotika Quran, 2021)
This paper explains the meaning of hijrah in Sayyid Qutb’s interpretation of fi Zhilal al-Qur’an. By using a descriptive-qualitative method and assisted by a maudhu’i interpretation approach, it is concluded that the meaning of hijrah according to Sayyid Qutub contains various meanings, including: hijrah in the sense of moving or leaving a country where the majority of heretics and infidels leave the country. Or a place filled with harmful things, whether it is for the safety of the soul, health of the body to avoid disease, and escape to save property. Sayyid Qutb also explained the types of hijrah that can be done today, among others: it can be done by taking education (seek knowledge), traveling to uphold Allah’s religion (jihad) and defending the country, as well as traveling to pick up sustenance.